Writing and Speaking Promotion based on Movies in GFL Classes in Jordan - Asali-van der Wal, Renata (Dirasat: Human and Social Sciences, 2019)
The study focuses on teachings of German Foreign Language by movies in German classes including writing and speaking of GFL classes in Jordan. The irrelevant social issues should not be shown to students in class as it helps in avoiding the consequences of social and cultural disparities. For promoting writing and speaking, feature films greatly influence some dimension of learning. The film adapted for the Jordanian German learners is titled ‘Short Sharp Shock’. The process of visualization for GFL learning activities of students in Jordan has a great impact on overall performance in their studies.